2020
DOI: 10.1074/jbc.ac120.015070
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for the interaction of Shiga toxin 2a with a C-terminal peptide of ribosomal P stalk proteins

Abstract: The principal virulence factor of human-pathogenic enterohemorrhagic Escherichia coli is Shiga toxin (Stx). Shiga toxin 2a (Stx2a) is the subtype most commonly associated with severe disease outcomes such as hemorrhagic colitis and hemolytic uremic syndrome. The catalytic A1 subunit (Stx2A1) binds to the conserved elongation factor binding C-terminal domain (CTD) of ribosomal P stalk proteins to inhibit translation. Stx2a holotoxin also binds to the CTD of P stalk proteins because the ribosome binding site is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 54 publications
2
36
0
Order By: Relevance
“…Although the interaction of P‐proteins and their C termini with external factors has been well documented from the structural point of view [24–26,42,50–52], no studies have been performed in relation to the role of their PTM. In our previous reports, we have demonstrated that P‐proteins form P1‐P2 heterodimers [18–20,34,53].…”
mentioning
confidence: 99%
“…Although the interaction of P‐proteins and their C termini with external factors has been well documented from the structural point of view [24–26,42,50–52], no studies have been performed in relation to the role of their PTM. In our previous reports, we have demonstrated that P‐proteins form P1‐P2 heterodimers [18–20,34,53].…”
mentioning
confidence: 99%
“…Seemingly, RTA exploits (and competes for) the pathways used by EFs to engage with the GTPase Associated Center and increase likelihood of encountering the SRL. This strategy may be conserved considering that other RIPs, such as Shiga toxin 2, have also been shown to bind to the CTD of ribosome P stalk proteins (46). While our focus up to this point has been on V9E1, it is just one of the nine VHHs identified in this study capable of neutralization of RTA in the IVT assay and interfering with RTA-P2C11 association.…”
Section: Discussionmentioning
confidence: 94%
“…Seemingly, RTA exploits (and competes for) the pathways used by EFs to engage with the GTPase-associated center and increase likelihood of encountering the SRL. This strategy may be conserved considering that other RIPs, such as Shiga toxin 2, have also been shown to bind to the C-terminal domain of ribosome P-stalk proteins ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…42 However, Stx2a formed a distinct P11-binding mode within a different surface pocket relative to RTA and TCS, suggesting different ribosome recognition mechanisms for each RIP. 42 Peptides mimicking the last 4 to 11 amino acids of P proteins bind to the P stalk binding site and inhibit depurination activity by disrupting RTA−ribosome interactions. 27 The P stalk binding site of RTA has not been previously targeted by small molecule inhibitors.…”
Section: ■ Introductionmentioning
confidence: 99%
“…A quadruple mutant, which combined alanine mutations in these residues with the R235A mutation, completely abolished the activity of RTA in mammalian cells, establishing the ribosome binding site as a new target for drug discovery . We recently reported the first X-ray crystal structure of Stx2a with P11 (PDB ID: 6X6H) and showed that, as observed with RTA, only the last six residues of P11 inserted into a shallow pocket on Stx2A1 . However, Stx2a formed a distinct P11-binding mode within a different surface pocket relative to RTA and TCS, suggesting different ribosome recognition mechanisms for each RIP …”
Section: Introductionmentioning
confidence: 99%